2017
DOI: 10.1128/aem.00823-17
|View full text |Cite
|
Sign up to set email alerts
|

Aerobiological Stabilities of Different Species of Gram-Negative Bacteria, Including Well-Known Biothreat Simulants, in Single-Cell Particles and Cell Clusters of Different Compositions

Abstract: The ability to perform controlled experiments with bioaerosols is a fundamental enabler of many bioaerosol research disciplines. A practical alternative to using hazardous biothreat agents, e.g., for detection equipment development and testing, involves using appropriate model organisms (simulants). Several species of Gram-negative bacteria have been used or proposed as biothreat simulants. However, the appropriateness of different bacterial genera, species, and strains as simulants is still debated. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
(64 reference statements)
2
11
0
Order By: Relevance
“…Glycerol is essentially non-volatile at the conditions tested in the present study, and may have protected the organism against desiccation in the gelatin filter and Mercer cascade impactor. These observations are consistent with previous studies that have shown both that bacterial survival during aerosolization is affected by the composition of the initial suspension medium [43][44][45], and that glycerol can have protective effects on microorganisms in aerosols [46]. While the suspension liquids used in the present study were laboratory media, the observed sensitivity to desiccation is consistent with published reports indicating that natural substrates which facilitate water retention, such as sputum or clay soils, tend to preserve viability of Burkholderia spp.…”
Section: Liquidsupporting
confidence: 93%
“…Glycerol is essentially non-volatile at the conditions tested in the present study, and may have protected the organism against desiccation in the gelatin filter and Mercer cascade impactor. These observations are consistent with previous studies that have shown both that bacterial survival during aerosolization is affected by the composition of the initial suspension medium [43][44][45], and that glycerol can have protective effects on microorganisms in aerosols [46]. While the suspension liquids used in the present study were laboratory media, the observed sensitivity to desiccation is consistent with published reports indicating that natural substrates which facilitate water retention, such as sputum or clay soils, tend to preserve viability of Burkholderia spp.…”
Section: Liquidsupporting
confidence: 93%
“…While SARS-CoV-2 is present in these particles, the vast majority of the particle mass is composed of other non-infectious, non-volatile components present in the suspension medium, with the virus representing only a small fraction of the particle mass. Therefore, the persistence of larger particle sizes which are known to be generated during other respiratory events, such as coughing or speaking (Chao et al 2009;Morawska et al 2009), should be investigated as the greater mass of non-infectious material associated with these particles has the potential to shield virus present within a particle from environmental insults, increasing its persistence in the environment (Dybwad and Skogan 2017;Kesavan et al 2013;Lighthart and Shaffer 1997). Another limitation of the present study relates to the particle composition of generated aerosols.…”
Section: Discussionmentioning
confidence: 99%
“…s c r i p t that the suspending medium can significantly affect the persistence of microorganisms(Dybwad and Skogan 2017). While the use of concentrated viral stocks was necessary to achieve quantifiable concentrations of infectious virus in the rotating drum chamber, the addition of the viral concentrate to the simulated saliva significantly changed both the protein content and fractional solids relative to the naïve simulated saliva.…”
mentioning
confidence: 99%
“…More attention should be given to total bacterial communities in precipitation due to the magnitude of their abundance, potential for terrestrial impact, likely effects on cloud glaciation, and non-uniform patterns of deposition in snowstorm events (Figure 4). We know that bacteria/archaea/eucarya can be viable in aerosols (59), suggesting that the multitude of taxa that we find in snow may be contributing to atmospheric chemistry in - situ around Earth. Given all of the bio-physical / chemical influences on the atmosphere, bio-precipitation should be considered just as complex and variable—and storm-track should be considered and essential component of this variance.…”
Section: Discussionmentioning
confidence: 98%